John and Elaine Steinbeck with friends at a beach picnic. - unknown:::Creator:::::::::::: (Sag Harbor, New York; United States, 2022)
John and Elaine Steinbeck at a beach picnic with Daga and Jack Ramsey and other friends. Nearby is Steinbeck's new four-wheel-drive Range Rover which got stuck on the beach. John didn't say a word between the time they arranged for help to come and when the tow truck driver showed up. Later asked why he was so quiet, John responded that he "was trying to think of something memorable to say to the tow truck driver because that's what people expected from him and word would get around."